Diplomasi Vaksin: Strategi Indonesia dalam Memperkuat Keamanan Kesehatan Nasional di Tengah Pandemi Covid-19 - Aldian Hidayat; Syaiful Anam; Ahmad Mubarak Munir (The Department of International Relations Universitas Mataram, 2022)
The COVID-19 pandemic has become a threat to national and global health issues. Not only health issues, but the Covid-19 pandemic also threatens various other crucial sectors such as the economy, security, social, and even global politics. Therefore, health issues are the main priority of every country during the Covid-19 pandemic. Vaccines are one way to increase human immunization and reduce the impact and spread of the virus. In order to obtain the availability of vaccines and national health facilities, the government of Indonesia has approached various countries and international forums both bilaterally and multilaterally through vaccine diplomacy. Indonesia's interest in this diplomacy is to obtain the availability of national vaccines and to participate in voicing and supporting other countries to obtain global vaccine availability. By using a qualitative approach, this paper analyzes the impact of the Covid-19 pandemic and Indonesia's strategy in dealing with this pandemic. Data collection techniques in research using library research. The theory used in this research is Vaccine Diplomacy, developed by Peter J. Hotez and Health Security from UNDP. Finally, this research found that through vaccine diplomacy, Indonesia was able to obtain the availability of vaccines to meet its national interests. With the availability of vaccines that had been obtained, Indonesia succeeded in carrying out the vaccination program to achieve the target of 70% of the national population, which was followed by the development of the national health level, which was marked by improving Indonesia's condition in various sectors, such as economy, tourism, education, social and even politics